The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jor.23129
|View full text |Cite
|
Sign up to set email alerts
|

Unique plasma metabolomic signature of osteonecrosis of the femoral head

Abstract: Metabolomic analysis was performed to determine the metabolomic signature of osteonecrosis of the femoral head (ONFH), and to investigate the underlying relationship between the metabolomic signature and the pathogenesis of ONFH. Plasma samples were collected from 30 ONFH patients and 30 normal subjects. The global metabolomic profile was obtained through a combination of high-throughput liquid-and gas-chromatography-based mass spectrometry analyses. All statistical analyses were conducted using the R software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Metabolites belonging to polyamine and urea pathway was also found to be deregulated 1 . Metabolomics of plasma of AVNFH showed 48 differentially regulated metabolites 23 while that of bone trabeculae showed 53 differentially regulated metabolites 25 . Pathway annotation analysis of these metabolites belonging to individual cohorts were carried out using MetaboAnalyst 30 .…”
Section: Proteomic Analysis Of Avnfh Bone Shows Deregulation In Multimentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites belonging to polyamine and urea pathway was also found to be deregulated 1 . Metabolomics of plasma of AVNFH showed 48 differentially regulated metabolites 23 while that of bone trabeculae showed 53 differentially regulated metabolites 25 . Pathway annotation analysis of these metabolites belonging to individual cohorts were carried out using MetaboAnalyst 30 .…”
Section: Proteomic Analysis Of Avnfh Bone Shows Deregulation In Multimentioning
confidence: 99%
“…Data from three published metabolomic analyses were used for our study. Our previous study involving targeted metabolomics of plasma samples from 14 patients compared to 14 healthy control samples were used 1 www.nature.com/scientificreports/ patients compared to 30 healthy controls 23 , and a bone trabecular metabolomics study of 28 patients compared to 20 controls 25 .…”
Section: Avnfh Gene Expression Microarray Proteomic and Metabolomicsmentioning
confidence: 99%
“…Bian et al reported that dexamethasone regulated lipid metabolism‐associated microRNAs in osteogenically induced human mesenchymal stem cells. Metabolomics analysis performed on 30 patients with GC‐induced ONFH and 30 healthy controls revealed that the abnormal metabolites induced by GCs were primarily in lipid‐, glutathione‐, nucleotide‐, and energy‐associated pathways …”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics analysis performed on 30 patients with GC-induced ONFH and 30 healthy controls revealed that the abnormal metabolites induced by GCs were primarily in lipid-, glutathione-, nucleotide-, and energy-associated pathways. 19 HDL and its major functional component apo-A1 counteract excessive cellular cholesterol accumulation and promote reverse cholesterol transport. In the present study, patients with lower baseline levels of HDL-C tended to have a higher risk of GC-induced ONFH (Fig.…”
Section: Hdl-c and Apo-b/apo-a1: Potential Predictive Value Of Lipid mentioning
confidence: 99%
“…In recent years, authors looking to embrace a consensus of opinion related to the pathogenesis of ONFH in their works have been devoting increasingly more attention to the importance of abnormal lipid metabolism 21. Research works over these years have supported the fact that ONFH is a problem of not merely local avascular status associated with bone necrosis but also including a systemic angle – in view of a significant contribution of hyperlipidemia 22.…”
Section: Discussionmentioning
confidence: 99%